An efficient synthesis of NaA zeolite membranes from direct crystallization of gel-dipped macroporous alumina tubes with seeds. Issue 22 (23rd May 2018) - Pan, Shuxiang; Meng, Xiangju; Wang, Zhengbao; Yan, Yushan; Xiao, Feng-Shou
Abstract : An efficient and sustainable synthesis of NaA zeolite membranes from direct crystallization of gel-dipped macroporous alumina tubes with seeds. Abstract : Compact NaA zeolite membranes are successfully synthesized by direct crystallization of gel-dipped macroporous Al2 O3 tubes. Before gel-dipping, NaA seeds are pasted on Al2 O3 tubes, followed by macropore-plugging with liquid. After the gel-dipping, a thin gel-layer formed on the Al2 O3 tube is directly crystallized into NaA zeolite membranes at 100 °C for 4 h in the absence of any excess liquid. The as-synthesized NaA membranes exhibit high pervaporation performance with a remarkable separation factor larger than 10 000 and high flux of 2.73 kg m −2 h −1 for dehydration of 90 wt% ethanol at 75 °C. This new efficient synthesis is potentially significant for preparation of high-performance, low-cost, and reproducible zeolite membranes.